Effect of Carbon Nanotubes and Graphene Oxide on the Hydration Characteristics and Compressive Strength of Cement Mortar with High Volume Fly Ash - Maizuar, Maizuar; Maulani, Emi; Usrina, Nura; Ersa, Nanda Savira; Sofyan, Sofyan; Mahmudy, Ash Shiddiq; Prasetia, Gigih (International Journal of Engineering, Science and Information Technology, 2025)
High-volume fly ash (HFVA) in cement mortar has gained attention due to its potential to reduce environmental impact and enhance sustainability. However, HVFA mortar often exhibits reduced initial compressive strength compared to conventional mortars. Incorporating carbon nanotubes (CNT) and Graphene oxide (GO) has been shown to enhance the mechanical properties and microstructure of the mortar, which can overcome the shortcomings of HVFA. This study investigates the effect of CNT and GO on compressive strength and cement hydration of HVFA mortar. This study used fly ash as a 60% cement replacement, with 0.01% CNT and GO contents of 0.01%, 0.02%, 0.03%, 0.04%, and 0.05%. Compressive strength tests were performed at 3, 7, and 28 days of curing. The results showed that adding CNT and GO improved the compressive strength by 15.4% over the control mortar at 0.01% CNT and 0.03% GO. Most importantly, incorporating CNT and GO mitigated the typical reduction in initial compressive strength, with around a 15% increase observed at 3 and 7 days compared to the control mortar. The cement hydration characteristics were analyzed using X-ray diffraction (XRD), which revealed the presence of various crystallization phases, including calcium silicate hydrate (C-S-H), calcium aluminate silicate hydrate (C-A-S-H), quartz, portlandite, calcium carbonate, and ettringite. Adding CNT and GO to HVFA mortar significantly enhances its mechanical properties. It promotes the formation of complete chemical bonds in the cement hydration process, improving the mortar's overall performance.